2007
DOI: 10.1007/s00383-007-2025-4
|View full text |Cite
|
Sign up to set email alerts
|

Bowel function after surgery for anorectal malformations in patients with tethered spinal cord

Abstract: Tethered spinal cord (TC) is an anomaly frequently recognized in association with anorectal malformations (ARM). However, the influence of TC on bowel function in children with ARM remains unknown. Furthermore, there are few studies that have assessed anorectal function in children with ARM and TC. The aim of this study was to evaluate anorectal function in ARM patients with TC using clinical assessment and anorectal manometry. Among 258 patients with ARM, this retrospective investigation included 35 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
2
8
0
6
Order By: Relevance
“…Correlation between spinal associated anomalies and outcome was not clear, because a poor response was reported even without these anomalies; however, if present, any patient had an excellent response. Regarding the SR, our analysis was apparently concordant with other study [26][27][28][29], because SR had high variability among similar patients and so, does not seems to be directly predictive of fecal incontinence after surgery, but it is certainly useful to predict the presence of spinal anomalies where this value is lower. Analyzing the data of patients singularly, we founded that patients with spinal anomaly have a lowest SR and they had a worse response to BFB therapy.…”
Section: Discussionsupporting
confidence: 87%
“…Correlation between spinal associated anomalies and outcome was not clear, because a poor response was reported even without these anomalies; however, if present, any patient had an excellent response. Regarding the SR, our analysis was apparently concordant with other study [26][27][28][29], because SR had high variability among similar patients and so, does not seems to be directly predictive of fecal incontinence after surgery, but it is certainly useful to predict the presence of spinal anomalies where this value is lower. Analyzing the data of patients singularly, we founded that patients with spinal anomaly have a lowest SR and they had a worse response to BFB therapy.…”
Section: Discussionsupporting
confidence: 87%
“…High-ARM patients had the lowest RP, with mean RP of 17 ± 7.7 and 21 ± 9.4 mm of Hg in infants and children group, respectively, thus explaining the reason for the poor clinical outcome in patients with high ARM owing to shorter sphincteric length and poor resting tone of anal canal. Similar observations of RP in ARM patients have been reported from other centers [12,15,16]. Anorectal sensory receptors reside either in rectum or in the pelvic floor.…”
Section: Discussionsupporting
confidence: 80%
“…17 The influence of a tethered cord on bowel dysfunction remains unknown in patients with ARM. 18 Recently, Tsuda et al 18 reported that bowel function after surgery for ARM did not differ significantly between those with or without a tethered cord. Jia et al 19 suggested that the causes of faecal incontinence may be a defect in the sacral parasympathetic nucleus innervation to the rectum during fetal development.…”
mentioning
confidence: 99%